Mechanical Evaluation of Two Grades of Titanium Used in Implant Dentistry - Hirata, Ronaldo; Bonfante, Estevam A.; Machado, Lucas S. [UNESP]; Tovar, Nick; Coelho, Paulo G. (Quintessence Publishing Co Inc, 2015)
Purpose: To investigate the effect of core dental implant materials supporting single crowns on the probability of survival and failure modes. Materials and Methods: Thirty-six standard external-hex titanium implants (4.0 mm in diameter) were selected to restore single crowns and divided into two groups according to core material: commercially pure grade 2 titanium (G2) and grade 5 titanium-aluminum-vanadium alloy (Ti-6Al-4V) (G5). Abutments were screwed to the implants, and standardized maxillary central incisor metal crowns were cemented and subjected to step-stress accelerated life testing in water. Use-level probability Weibull curves and reliability for missions of 100,000 cycles at 150 N and 200 N (with 90% two-sided confidence intervals [CIs]) were calculated. Polarized light and scanning electron microscopes were used to determine the failure modes. Results: Use-level probability Weibull calculations showed beta values of 0.59 (CI, 0.31 to 1.11) and 1.22 (CI 0.81 to 1.84) for G2 and G5, respectively, and significantly higher characteristic strength and Weibull modulus for G5. The calculated reliability (90% CIs) for a mission of 100,000 cycles at 150 N showed that cumulative damage would lead to survival of 45% of implant-supported crowns of G2 and 98% of G5. At 200 N the probability of survival decreased to 0.03% for G2 and 21% for G5. Abutment screw fracture was the failure mode for all groups. Conclusion: Reliability, characteristic strength, and Weibull modulus were significantly higher for Ti-6Al-4V dental implants than for commercially pure (grade 2) titanium implants. Failure modes were similar for both groups.
Keywords: biomechanics; dental implants; failure testing; fatigue testing; reliability; Weibull curves